Investigação sobre materiais manipuláveis e jogos de matemática utilizados por professores no ensino de crianças surdas nos anos iniciais - Fernando, Odete Agostinho (2015)
This dissertation discusses how manipulable materials and games have been used in math education for deaf children. The question of this work was: how games and manipulative materials are used in mathematics education for deaf children? To answer this and other questions, interviews were conducted with teachers of three deaf education centers. The general objective was to analyze the games and manipulative materials used by math teachers in deaf education in schools of Cascavel and Foz do Iguaçu. To choose the schools the following criteria were used: only schools for the deaf, bilingual schools, schools where teachers use games to teach mathematics to deaf students. First, is presented a historical summary about deaf education and the main approaches: oralism, total communication and bilingualism. The oralist approach defends the teaching of oral speech for the deaf. Total communication defends all types of communication during the educational process of the deaf. Total communication is not recommended, because isn't systematized. In this work the bilingualism is defended. Bilingualism starts with the teaching of the sign language as the first language and of the written form of the portuguese as second language. In order to teach deaf students is necessary to consider that they learn different than listeners. Deaf people need a sensorial education. To address the games and manipulative materials in mathematics education, the theories of Piaget and Vygotsky are adopted. Piaget is the starting point to understand the play and its role in the construction of the number. Vygotsky's theory helps to understand the importance of sign language for a meaningful teaching to the deaf child. We conclude that the games are indispensable in the lives of deaf and hearing children, as they influence the development and the construction of the number.